2021
DOI: 10.1002/da.23150
|View full text |Cite
|
Sign up to set email alerts
|

Reduced neural differentiation of rewards and punishment during passive avoidance learning in adolescents with generalized anxiety disorder

Abstract: Background: It has been proposed that individuals with generalized anxiety disorder (GAD) show dysfunctional computations related to approach-avoidance decisionmaking. However, few studies have examined the neural basis of this impairment, particularly in adolescents with GAD. The goal of the current study was to address this gap in the literature. Method: The study involved 51 adolescents with GAD and 51 typically developing (TD) comparison individuals matched on age (16.10 and 15.75 respective means), gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The current results may also be relevant to understand the development of psychopathology following life stress exposure as they suggest that individuals with a smaller RewP may be limited in their ability to display PA in response to positive events—thus making them more susceptible to the effects of stress. Abnormal neural response to rewards have been observed in depression (Kendler et al, 1999; Proudfit, 2015; Tennant, 2002), generalized anxiety disorder (Bashford‐Largo et al, 2021; Kessel et al, 2015), psychosis and schizophrenia (Van Winkel et al, 2008; Waltz et al, 2009; Whitton et al, 2015), substance abuse (Baker, Stockwell, et al, 2016; Baker, Wood, & Holroyd, 2016; Joyner et al, 2019), problem gambling (Hewig et al, 2010; Oberg et al, 2011), as well as in individuals at risk for these disorders (Bart et al, 2021; Bress et al, 2013; Burani et al, 2021; Cope et al, 2019; Foti et al, 2011; Gruber et al, 2018). Each of these disorders is also frequently precipitated by stress exposure (Burani et al, 2021; Kendler et al, 1999; Koob, 2008; McCreary & Sadava, 2000; Monroe & Harkness, 2005; Myin‐Germeys et al, 2001; Pizzagalli, 2014; Pizzagalli et al, 2007; Van Winkel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The current results may also be relevant to understand the development of psychopathology following life stress exposure as they suggest that individuals with a smaller RewP may be limited in their ability to display PA in response to positive events—thus making them more susceptible to the effects of stress. Abnormal neural response to rewards have been observed in depression (Kendler et al, 1999; Proudfit, 2015; Tennant, 2002), generalized anxiety disorder (Bashford‐Largo et al, 2021; Kessel et al, 2015), psychosis and schizophrenia (Van Winkel et al, 2008; Waltz et al, 2009; Whitton et al, 2015), substance abuse (Baker, Stockwell, et al, 2016; Baker, Wood, & Holroyd, 2016; Joyner et al, 2019), problem gambling (Hewig et al, 2010; Oberg et al, 2011), as well as in individuals at risk for these disorders (Bart et al, 2021; Bress et al, 2013; Burani et al, 2021; Cope et al, 2019; Foti et al, 2011; Gruber et al, 2018). Each of these disorders is also frequently precipitated by stress exposure (Burani et al, 2021; Kendler et al, 1999; Koob, 2008; McCreary & Sadava, 2000; Monroe & Harkness, 2005; Myin‐Germeys et al, 2001; Pizzagalli, 2014; Pizzagalli et al, 2007; Van Winkel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Fear of uncertainty: People with GAD frequently have a high intolerance for uncertainty, which hinders their ability to make decisions in ambiguous situations [41][42][43][44].…”
Section: Empirical Studiesmentioning
confidence: 99%
“…One fMRI study of AAC in adolescents with generalized anxiety disorder found reduced responsivity to rewards and punishment in the striatum (i.e., caudate and putamen) compared to typically developing adolescents, but no neural differences during decision-making. 31 Given the high comorbidity of anxiety and depression, [32][33][34][35] studies of AAC decision-making could be useful for delineating transdiagnostic and disorder-specific disruptions.…”
Section: E312mentioning
confidence: 99%